PERTUMBUHAN BURUNG PUYUH (COTURNIX COTURNIX JAPONICA) UMUR 3 MINGGU DENGAN PERBEDAAN KEPADATAN DI DALAM KANDANG - Syukri I Gubali (Animal Husbandry Department, Faculty of Agriculture Gorontalo State University, 2021)
The purpose of this study was to determine the growth of quail aged 3 weeks, based on different cage densities. Completely randomized design was used during the study, with the density of quails in cages were 11 (P1), 13 (P2), 16 (P3), and 20 (P4). The results showed that differences in quail density in cages affected (P0.05) body weight, consumption, and conversion of quail during rearing. the number of quail in the cage is 11 for a cage size of 35x30x40 cm. Body weight, consumption, and conversion of feed produced at 3 weeks of age were: 95.52 gr, 12.53 gr, 0.13